Application of E-Learning to Support Teacher and Student Productivity During the Pandemic - Fikri Fajar Muttaqin; Ade Dwi Putra (Jurnal Teknologi dan Sistem Informasi, 2023)
One of the schools that has not implemented the concept of online learning is SDN 1 Bandar Dalam, located in South Lampung Regency, which was established in 1977 with 258 students and 13 teachers. problems in the form of the learning process carried out through whatsapp media are still considered less than optimal. The difficulty in using it is that the material presented is not explained clearly which affects students who do not understand it. The next problem is the attendance process based on the given task so that it is not in accordance with the concept of learning. Parents are so worried about information about seeds and students attending the recitation, because the results of the assignments and comings given have not been recorded as a form of livelihood. The system development method used is an extreme program with the concept of object orientation. The result of the research is that the concept of online learning is built using a website so that the learning process during the pandemic can still be productive when teaching teachers to students. The resulting learning system applications such as being able to manage data for teachers, students, subjects, classes, the teacher section can provide material and questions, the student section can participate in discussions about the material by displaying information such as material files, links to streaming media and displaying material info via videos.